Sifat Fisika Tanah pada Lahan Sawah Pasang Surut dengan Olah dan Tanpa Olah Tanah di Kebun Percobaan BPSIP Kabupaten Kubu Raya - Uljanah, Nisa; Junaidi, Junaidi; Hazriani, Rini (Soil Science Department, Faculty of Agriculture, Tanjungpura University, 2025)
Land preparation to start the rice planting season in the Experimental Garden applies tillage and no-tillage systems. This study aims to assess the differences in soil physical properties on tidal rice fields with tillage and no-tillage systems in the Experimental Farm of BPSIP Kubu Raya Regency. Soil sampling used the transect method and there were 5 observation points at each soil sampling location. Soil samples were taken at a depth of 0-20 cm and 20-40 cm which are intact soil samples and disturbed soil samples while soil aggregate samples were taken at a depth of 0-20 cm. The parameters of soil physical properties include soil fraction, bulk density, total porosity, permeability rate, field capacity water content, and aggregate stability. The results showed that there were no differences in soil physical properties in tidal rice fields with tillage and no-tillage surjan systems in all soil physical properties parameters, except for the soil aggregate stability parameter which showed significantly different results, no-tillage rice fields had higher values than tillage rice fields.